Adjuvant therapy following oesophagectomy for adenocarcinoma in patients with a positive resection margin. Issue 13 (29th September 2020) - Bott, R. K.; Beckmann, K.; Zylstra, J.; Wilkinson, M. J.; Knight, W. R. C.; Baker, C. R.; Kelly, M.; Maisey, N.; Qureshi, A.; Sevitt, T.; Van Hemelrijck, M.; Smyth, E. C.; et al.
Abstract : Background: The role of adjuvant therapy in patients with oesophagogastric adenocarcinoma treated by neoadjuvant chemotherapy is contentious. In UK practice, surgical resection margin status is often used to classify patients for receiving adjuvant treatment. The aim of this study was to assess the survival benefit of adjuvant therapy in patients with positive (R1) resection margins. Methods: Two prospectively collected UK institutional databases were combined to identify eligible patients. Adjusted Cox regression analyses were used to compare overall and recurrence‐free survival according to adjuvant treatment. Recurrence patterns were assessed as a secondary outcome. Propensity score‐matched analysis was also performed. Results: Of 616 patients included in the combined database, 242 patients who had an R1 resection were included in the study. Of these, 112 patients (46·3 per cent) received adjuvant chemoradiotherapy, 46 (19·0 per cent) were treated with adjuvant chemotherapy and 84 (34·7 per cent) had no adjuvant treatment. In adjusted analysis, adjuvant chemoradiotherapy improved recurrence‐free survival (hazard ratio (HR) 0·59, 95 per cent c.i. 0·38 to 0·94; P = 0·026), with a benefit in terms of both local (HR 0·48, 0·24 to 0·99; P = 0·047) and systemic (HR 0·56, 0·33 to 0·94; P = 0·027) recurrence. In analyses stratified by tumour response to neoadjuvant chemotherapy, non‐responders (Mandard tumour regression grade 4–5) treated with adjuvant chemoradiotherapy had an overall survival benefit (HR 0·61, 0·38 to 0·97; P = 0·037). In propensity score‐matched analysis, an overall survival benefit (HR 0·62, 0·39 to 0·98; P = 0·042) and recurrence‐free survival benefit (HR 0·51, 0·30 to 0·87; P = 0·004) were observed for adjuvant chemoradiotherapy versus no adjuvant treatment. Conclusion: Adjuvant therapy may improve overall survival and recurrence‐free survival after margin‐positive resection. This pattern seems most pronounced with adjuvant chemoradiotherapy in non‐responders to neoadjuvant chemotherapy. Abstract : In UK practice, surgical resection margin status is often used to stratify patients for receipt of adjuvant treatment. This cohort study suggested both an overall and recurrence‐free survival benefit following adjuvant therapy in patients with positive margins, who had undergone neoadjuvant chemotherapy and resectional surgery for oesophageal adenocarcinoma. The benefit seemed greater with adjuvant chemoradiotherapy and in poor responders to neoadjuvant chemotherapy. Decreases recurrence and improves survival Abstract : Antecedentes: El papel del tratamiento adyuvante en pacientes con adenocarcinoma esofagogástrico tratados con quimioterapia neoadyuvante es polémico. En la práctica del Reino Unido, el estado del margen de resección quirúrgico se utiliza a menudo para identificar a los pacientes que reciben tratamiento adyuvante. El objetivo de este estudio fue evaluar el beneficio en la supervivencia del tratamiento adyuvante en pacientes con márgenes de resección positivos (R1). Métodos: Se combinaron dos bases de datos de instituciones del Reino Unido que recogen información de forma prospectiva para identificar pacientes elegibles. Se utilizaron análisis de regresión de Cox ajustados para comparar la supervivencia global y la supervivencia libre de recidiva según el tratamiento adyuvante. Los patrones de recidiva se evaluaron como resultado secundario. También se realizó un análisis de emparejamiento por puntaje de propensión. Resultados: De 616 pacientes incluidos en la base de datos combinada, se incluyeron en el estudio 242 pacientes con resección R1. De estos pacientes, 112 (46%) recibieron quimiorradioterapia adyuvante, 46 (19%) pacientes fueron tratados con quimioterapia adyuvante y 84 (35%) pacientes no recibieron ningún tratamiento. En el análisis ajustado, la quimiorradioterapia adyuvante mejoró la supervivencia libre de recidiva (cociente de riesgos instantáneos, hazard ratio, HR 0, 59, i.c. del 95% 0, 38‐0, 94; P = 0, 026) con un beneficio tanto para la recidiva local (HR 0, 48, i.c. del 95% 0, 24‐0, 99; P = 0, 047) como para la sistémica (HR 0, 56, i.c. del 95% 0, 33‐0, 94; P = 0, 027). Cuando los pacientes se clasificaron según la respuesta tumoral a la quimioterapia neoadyuvante, los no respondedores (Mandard Grado 4/5) tratados con quimiorradioterapia adyuvante obtuvieron un beneficio en la supervivencia (HR 0, 61, i.c. del 95% 0, 38‐0, 97; P = 0, 037). En el análisis por emparejamiento por puntaje de propensión, se observó un beneficio en la supervivencia global (HR 0, 62, i.c. del 95% 0, 39‐0, 98; P = 0, 042) y en la supervivencia libre de recidiva (HR 0, 51.i.c. del 95% 0, 30‐0, 87; P = 0, 004) con la quimiorradioterapia adyuvante frente a no recibir tratamiento adyuvante. Conclusión: El tratamiento adyuvante puede mejorar la supervivencia global y la supervivencia libre de recidiva en pacientes con margen de resección positivo. Este patrón parece más pronunciado con la quimiorradioterapia adyuvante en pacientes que no responden a la quimioterapia.